Cover crop nitrogen contribution to organic broccoli production. Issue 1 (20th February 2020) - Luna, John M.; Sullivan, Dan; Garrett, Amy M.; Xue, Lan
Abstract: Nitrogen (N) is a difficult nutrient to manage in organic farming systems, and yield reductions related to N deficiency have been reported in organic systems. Legume-based cover crops offer opportunities for biologically fixed N; however, improved quantification of N contribution is needed for cost-effective N management. A 2-yr experiment was conducted near Corvallis, OR, USA, in 2007 and 2008 to (1) evaluate biomass production and N accumulation from selected cover crop treatments, (2) compare the effects of fall-planted cover crops on broccoli [( Brassica oleraceae L. (Italica group)] yield, (3) estimate the quantity of feather meal-N replaced by cover crops. Cover crop treatments included common vetch ( Vicia sativa L.), phacelia ( Phacelia tanacetifolia Benth), oats ( Avena sativa L.) and the mixtures phacelia plus vetch, oats plus vetch and a no-cover crop (fallow) treatment as the control. Using feather meal as an N source, four rates of N fertilizer (0, 100, 200 and 300 kg N ha −1 ) were randomized within each cover crop treatment in a randomized, split-plot design. Cover crop biomass and N accumulation differed between the 2 yr of the study. In 2007, total biomass accumulation ranged from 5000 to 10, 000 kg ha −1, whereas in 2008, cover crop accumulation was 1500 to 5000 kg ha −1 . Biomass of both phacelia and vetch (in mixtures or as sole crops) was reduced by 80% from 2007 to 2008, whereas oat biomass and weed biomass in the fallow plots was reduced by only 40% between the 2 yr. The accumulation of N was also reduced in 2008, with vetch (either as a sole crop or in mixtures) contributing less than a third of total N produced in 2007. In 2007, vetch and vetch-based cover crop mixtures increased broccoli yield compared with the fallow, providing 100–135 kg fertilizer equivalent N ha −1 . But due to decreased cover crop biomass and N accumulation in 2008, vetch and vetch-based mixtures failed to increase broccoli yield, providing <20 kg N ha −1 fertilizer equivalence. In 2007, oats grown as a sole cover crop reduced broccoli yield when no supplemental N was applied. In 2008, both phacelia and oats reduced broccoli yield at all N levels, with estimated N fertilizer equivalence values of −80 to −95 kg N ha −1 . Although legume and legume mixtures increased broccoli yield in only 1 yr of the experiment, addition of vetch to the mixtures reduced yield loss in both years compared with oats and phacelia grown as sole crops.